2022
DOI: 10.1108/josm-09-2021-0345
|View full text |Cite
|
Sign up to set email alerts
|

Robotic role theory: an integrative review of human–robot service interaction to advance role theory in the age of social robots

Abstract: PurposeSocial robots increasingly adopt service roles in the marketplace. While service research is beginning to unravel the implications for theory and practice, other scientific disciplines have amassed a wealth of empirical data of robots assuming such service roles. The purpose of this paper is to synthesize these findings from a role theory perspective with the aim of advancing role theory for human–robot service interaction (HRSI).Design/methodology/approachA systematic review of more than 10,000 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 85 publications
(209 reference statements)
0
6
0
Order By: Relevance
“…For example, Scott et al (2013) concluded that when role congruity was achieved between the consumer and the seller, customer attitude and behavioral intentions were positively influenced. Furthermore, Blaurock et al (2022) extended the literature on role theory by providing a framework of the role theory in a human–robot service interaction context. Lastly, Kim et al (2022) applied the role theory with respect to relationships among brand modernity, brand love and behavioral intentions, and they analyzed the interactions between human and robot service providers with consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Scott et al (2013) concluded that when role congruity was achieved between the consumer and the seller, customer attitude and behavioral intentions were positively influenced. Furthermore, Blaurock et al (2022) extended the literature on role theory by providing a framework of the role theory in a human–robot service interaction context. Lastly, Kim et al (2022) applied the role theory with respect to relationships among brand modernity, brand love and behavioral intentions, and they analyzed the interactions between human and robot service providers with consumers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, customers are far from being the only stakeholders affected by this technological revolution in the service industry. Although often overlooked, frontline employees are also impacted by the increasing adoption of robots by service firms (Blaurock et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The higher the level of intelligence built into these robots, the more capable they are of supporting frontline employees, increasing the likelihood that they will replace these human employees (Huang and Rust, 2018). From the perspective of frontline employees, the presence of these service robots will notably change how they perform their work and could substantially modify their roles and responsibilities in the workplace (Blaurock et al. , 2022; Bonekamp and Sure, 2015; Kipper et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations